1985
DOI: 10.1128/jcm.21.4.654-655.1985
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an organism resembling Clostridium barati which produces type F botulinal toxin from an infant with botulism

Abstract: All reported casçs of infant botulism except one have been caused by proteolytic strains (group I) of Clostridium botulinum, toxin types A or B. We describe the cultural and biochemical characteristics of the causative organism of this singular case of infant botulism, caused by type F botulinal toxin. Although this organism produces type F botulinal toxin, it is quite different from proteolytic (group 1) C. botulinum, being more closely related to Clostridium barati.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
4

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(60 citation statements)
references
References 5 publications
2
54
0
4
Order By: Relevance
“…proteolytic strains) whilst in other cases the same toxin type is produced by different genotypes (BoNT types B and F). Recently some strains of C. barati Table 1 Comparison of percentage sequence similarities (lower left hand triangle) and total number of nucleotide differences (upper right hand triangle) for a 1516nucleotide region of 16S rRNA of saccharolytic C. botulinum and other clostridia and C. butyricum have been shown to produce BoNT (types F and E respectively; [5][6][7]) and which by definition are now considered to be C. botulinum. In view of the above taxonomic complexities and the clinical and veterinary importance of C. botulinum there is an urgent need to determine the precise genetic interrelationships of members of this species complex.…”
Section: Introductionmentioning
confidence: 99%
“…proteolytic strains) whilst in other cases the same toxin type is produced by different genotypes (BoNT types B and F). Recently some strains of C. barati Table 1 Comparison of percentage sequence similarities (lower left hand triangle) and total number of nucleotide differences (upper right hand triangle) for a 1516nucleotide region of 16S rRNA of saccharolytic C. botulinum and other clostridia and C. butyricum have been shown to produce BoNT (types F and E respectively; [5][6][7]) and which by definition are now considered to be C. botulinum. In view of the above taxonomic complexities and the clinical and veterinary importance of C. botulinum there is an urgent need to determine the precise genetic interrelationships of members of this species complex.…”
Section: Introductionmentioning
confidence: 99%
“…Recent 16S rRNA sequencing studies [5] have shown that proteolytic C. botulinurn type F is phylogenetically only remotely related to non-proteolytic C. botulinum type F and C. barati. There are now other C. barati strains that have been shown to produce BoNT/F [4,6,7] Table 1 genotypes (e.g. proteolytic and non-proteolytic) may also provide valuable information on the evolutionary interrelationships of the BoNTs.…”
Section: Discussionmentioning
confidence: 99%
“…BoNT type B is produced by saccharolytic and proteolytic genotypes). The classification of C. botulinum has been further complicated by reports of neurotoxins produced by some strains of C. barati [6,7] and C. butyricum [8,9] that cross-react with antisera raised against BoNT types F and E respectively. The genospecific authenticity of these strains has been confirmed by definitive molecular techniques [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Members of group I are proteolytic, members of group II are nonproteolytic and can grow and produce toxin at refrigerated temperature (i.e., 3 C). Group III members produce toxin types C and D, and group IV produce serological type G toxin, and some nontoxigenic clostridia are also placed in this group (Hall et al, 1985;Adams and Moss, 2008). Botulism is widely distributed in many parts of the world, as C. botulinum is a soil saprophyte.…”
Section: Clostridium Botulinummentioning
confidence: 99%